Pharmacist Interventions in Minimizing Drug Related Problems in Diabetes With Co-Existing Hypertension: A Five-Year Overview and Ground Report From India - Ian Osoro; Mohammed Amir; Manisha Vohra; Amit Sharma (Frontiers Media S.A., 2023)
Objective: The study aimed to investigate the pharmacist interventions in minimizing drug-related problems in diabetes with co-existing hypertension.Methods: Prospective observational study.Results: Overall, a total of 628 interventions were recommended for 1,914 patients during the 5-year period of study. Among all the interventions, the majority were suggested regarding "substituting the drug" (39%), change in frequency of administration (25%), and addition of drug (14%). Patient compliance status was found significant (p = 0.29 ± 0.07).Conclusion: Clinical pharmacists have a crucial role in minimizing drug related problems. Particularly, there should be a greater emphasis on patient counselling and patient follow-up.